2006
DOI: 10.1074/jbc.m513569200
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Sulfur Cluster Biosynthesis

Abstract: The biogenesis of iron-sulfur [Fe-S] clusters requires the coordinated delivery of both iron and sulfide. Sulfide is provided by cysteine desulfurases that use L-cysteine as sulfur source. So far, the physiological iron donor has not been clearly identified. CyaY, the bacterial ortholog of frataxin, an iron binding protein thought to be involved in iron-sulfur cluster formation in eukaryotes, is a good candidate because it was shown to bind iron. Iron-sulfur [Fe-S] clusters are ubiquitous and evolutionary anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
114
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(121 citation statements)
references
References 60 publications
7
114
0
Order By: Relevance
“…Moreover, broad distributions of FXN were observed in heart tissue extract, suggesting that oligomeric forms of the protein were also present in vivo (30). In addition, the ability to oligomerize enabled the E. coli and yeast frataxin homologues (CyaY and Yfh1) to detoxify iron and promote Fe-S cluster assembly (31)(32)(33)(34). We reasoned that this property should be maintained in human cells, if not by FXN , by another as yet undefined FXN isoform.…”
Section: From the Departments Of Pediatric And Adolescent Medicine And mentioning
confidence: 99%
“…Moreover, broad distributions of FXN were observed in heart tissue extract, suggesting that oligomeric forms of the protein were also present in vivo (30). In addition, the ability to oligomerize enabled the E. coli and yeast frataxin homologues (CyaY and Yfh1) to detoxify iron and promote Fe-S cluster assembly (31)(32)(33)(34). We reasoned that this property should be maintained in human cells, if not by FXN , by another as yet undefined FXN isoform.…”
Section: From the Departments Of Pediatric And Adolescent Medicine And mentioning
confidence: 99%
“…In human cells data indicate that the interaction is mediated by Isd11 (20). In the case of bacteria, which do not have an Isd11 homolog, the available data indicate that the cysteine desulfurase Nfs1, the ortholog of eukaryotic IscS, is necessary for the interaction (21).…”
mentioning
confidence: 99%
“…Conversely, Nfs1 and the low levels of Isu1 initially present in ϳ80 -670-kDa fractions shifted to the highest of these fractions (Fig. 3, L versus M and N versus O), possibly reflecting interactions of the Nfs1-Isu1 complex with ironloaded Yfh1 oligomers, as observed for bacterial frataxin in vitro (8). Thus, the broad molecular mass shift exhibited by FIGURE 2.…”
Section: Strainmentioning
confidence: 87%
“…Although one group reported that Yfh1 oligomerization is dispensable in vivo (38), we later showed that mutations affecting Yfh1 assembly are asymptomatic in unstressed cells but become harmful during stress exposure and cause synthetic lethality in cells lacking copper-zinc superoxide dismutase (34). Iron-dependent assembly has also been characterized for the Escherichia coli orthologue, CyaY, and shown to be required for interaction of CyaY with the ISC assembly proteins IscU and IscS in vitro (8,39). Unlike the yeast or E. coli orthologues, human frataxin assembles at physiological iron concentrations during expression in E. coli or in human heart but not in vitro (40,41), indicating that different mechanisms govern frataxin assembly in different species.…”
mentioning
confidence: 99%
See 1 more Smart Citation